Simultaneous responses of photosystem II and soluble proteins of rapeseed to cold acclimation - Arminian, Ali; Dehghani Bidgoli, Reza (Cellular and Molecular Biology, 2019)
This experiment was conducted to assess the quantitative and qualitative changes in soluble proteins as well as some chlorophyll fluorescence parameters in the leaves of a winter canola (Brassica napus L., cv. Licord) under continuous low temperature. Over the experiment, seedlings were initially grown at 15/10 °C (d/n). At fourth fully expanded leafy stage (day 30), a part of the plants were transferred to 4/2°C for 4 weeks. Plants were sampled for protein extraction from leaves in which chlorophyll fluorescence parameters (Fo, Fv, Fm, Fv/Fo, Fm/Fo, Fv/Fm, Fo´, FV´, Fm´ and some other calculated) were also measured. The results showed a clear increase in soluble proteins quantity caused by cold treatment. The enhancements appeared abruptly following the cold exposure to 4°C and lasted. The electrophoretic protein patterns showed changes in the intensity of some polypeptides, besides, induction a new probable protein weighing 47-kW in response to cold treatment. Cold-triggered reduction in maximum quantum yield of PSII (Fv/Fm) was connected especially with drastic decreasing Fv and Fm. Interestingly, high quantitative amounts of soluble proteins along with induction of the new probable polypeptide induced at cold temperature, were attributed to low deduction of maximum quantum yield of PSII. Additionally, more imperative chlorophyll fluorescence parameters changed e.g. qP, NPQ, qL, Y(II) or Ñ„PSII etc at light. Nowadays, radar charts or spider plots are the most sophisticated multivariate statistical tools representing physiological responses of plants to abiotic stress conditions or even morphophysiological studies of plants. In rapeseed many researches performed by applying the radar charts for low temperature stresses and interpreted their effects more advancely than common statistical tools. We observed a good representation of the chl fluorescence parameters fluctuations using radar plots. Overall, cold-induced soluble proteins accumulated after longer cold-acclimation, can contribute in photosynthetic apparatus protection against low-temperature damages.